Implementation of Local Government Information System in Improving the Quality of Development Planning in Jembrana Regency, Indonesia - Suardiyanti, Ni Luh Putu; Aripin, Sofjan; Widnyani , Ida Ayu Putu Sri (Golden Ratio of Social Science and Education, 2025)
This study aims to analyze the implementation of SIPD to improve the quality of regional development planning in Jembrana Regency. Since the enactment of Permendagri Number 70 of 2019, the Jembrana Regency Government has faced several obstacles in using SIPD to support the preparation of regional development planning documents, including limited resources, the absence of standard implementation procedures in the region, and low human resource capacity which results in suboptimal data input and implementation of the planning process flow in SIPD. This study used a descriptive qualitative approach, using data from interviews, observations, and documentation studies. The results of the study indicate that the implementation of the SIPD policy in Jembrana Regency has not been optimal in several dimensions that still face obstacles, namely aspects of implementer competence and capability, aspects of resource support, aspects of strategies applied, and aspects of implementer compliance and responsiveness in implementing SIPD. The less than optimal implementation of this policy is caused by several inhibiting factors, including the low capacity of implementers in terms of both quantity and quality, the unfulfilled standards for the number of human resources, the capacity of the system network support, and the availability of budget, the weak coordination strategy used, and the lack of compliance and responsiveness of policy implementers both in Bappeda and in each Regional Apparatus. Bappeda needs to focus on strengthening the capacity of implementers through technical training, socialization, mentoring, and the preparation of clear standard procedures to facilitate monitoring and evaluation. In addition, coordination in the form of FGDs and socialization with OPDs, DPRD, and the community needs to be carried out at every stage of the planning process so that there is no conflict of interest and resistance to SIPD policies in the future. Bappeda can also innovate in the form of planning clinics to facilitate the Regional Apparatus in consulting regarding SIPD planning and implementation. The Ministry of Home Affairs must also ensure network infrastructure support so that this system does not experience problems when accessed simultaneously.